A fungal microRNA‐like RNA subverts host immunity and facilitates pathogen infection by silencing two host receptor‐like kinase genes. Issue 6 (18th January 2022) - Xu, Ming; Li, Guangyao; Guo, Yan; Gao, Yuqi; Zhu, Lihua; Liu, Zhaoyang; Tian, Runze; Gao, Chen; Han, Pengliang; Wang, Ning; Guo, Feiran; Bao, Jiyuan; et al.
Summary: Small RNAs (sRNAs) play important roles in various biological processes by silencing their corresponding target genes in most eukaryotes. However, cross‐kingdom regulation mediated by fungal microRNA‐like RNAs (milRNAs) in plant–pathogen interactions is still largely unknown. Using molecular, genetic, histological, and biochemical approaches, we found that the apple tree Valsa canker pathogen Valsa mali milRNA Vm ‐milR1 could suppress the host immunity by silencing two host receptor‐like kinase genes, MdRLKT1 and MdRLKT2 . Vm ‐milR1 was highly induced during V. mali infection. Deletion of Vm ‐milR1 precursor abolished the generation of Vm ‐milR1 and reduced the virulence of V. mali . Inoculation of Vm ‐milR1 deletion mutants induced the host defence responses, including reactive oxygen species (ROS) accumulation, callose deposition, and high expression of defence‐related genes. Furthermore, Vm ‐milR1 was confirmed to be able to suppress the expression of MdRLKT1 and MdRLKT2 in a sequence‐specific manner. Moreover, overexpression of either MdRLKT1 or MdRLKT2 enhanced apple resistance to V. mali by activating the host defence responses. Furthermore, knockdown of MdRLKT1 or MdRLKT2 compromised the host resistance to V. mali . Our study revealed that V. mali was equipped with Vm ‐milR1 as an sRNA effector to silence host receptor‐like kinase genes, suppress the host defence responses, and facilitate pathogen infection.